The impact of a view from a window on thermal comfort, emotion, and cognitive performance - Ko, Won Hee; Schiavon, Stefano; Zhang, Hui; Graham, Lindsay T.; Brager, Gail; Mauss, Iris; Lin, Yu-Wen (Building and environment, 2020)
Visual connection to nature has been demonstrated to have a positive impact on attention restoration, stress reduction, and overall health and well-being. Inside buildings, windows are the primary means of providing a connection to the outdoors, and nature views even through a window may have similar effects on the occupants. Given that humans recognize environments through multi-sensory integration, a window view may also affect occupants’ thermal perception. We assessed the influence of having a window with a view on thermal and emotional responses as well as on cognitive performance. We conducted a randomized crossover laboratory experiment with 86 participants, in spaces with and without windows. The chamber kept the air and window surface temperature at 28 °C, a slightly warm condition. The outcome measures consisted of subjective evaluations (e.g., thermal perception, emotion), skin temperature measurements and cognitive performance tests. In the space with versus without windows, the thermal sensation was significantly cooler (0.3 thermal sensation vote; equivalent to 0.74 °C lower), and 12% more participants were thermally comfortable. Positive emotions (e.g., happy, satisfied) were higher and negative emotions (e.g., sad, drowsy) were lower for the participants in the window versus the windowless condition. Working memory and the ability to concentrate were higher for participants in the space with versus without windows, but there were no significant differences in short-term memory, planning, and creativity performance. Considering the multiple effects of window access, providing a window with a view in a workplace is important for the comfort, emotion, and working memory and concentration of occupants. [Display omitted] •We conducted a randomized crossover experiment with 86 participants.•At a slightly warm condition, people felt cooler and more comfortable with windows.•Positive emotions increased while negative emotions decreased with windows.•Participants' working-memory and concentration improved in a space with windows.•Having windows did not affect short-term, planning and creativity performance.